Youth and Adult Education in times of pandemic in remote mode, reinventing the way to study and overcoming new challenges (Research, Society and Development, 2022)
The high dropout rates of students in the Youth and Adult Education (EJA) modality drew attention at the time of the pandemic. Before, there were already a lot of school dropouts, and with the context of remote teaching, dropouts in EJA have increased. There are some factors that may have aggravated this increase in school dropout, such as the lack of access and domain of the internet in the digital world, the lack of financial resources and the routine of heavy and exhausting work. Here, we sought to elucidate the problem that prevents students of this modality from staying in school. For this, a questionnaire was used as a data collection instrument (electronic form), in which an interview was conducted to investigate the causes of the increase in EJA school dropout during the pandemic period. In their answers, the students expressed their anxieties regarding remote teaching, their difficulties in carrying out the activities of the PETs were addressed; factors related to dropping out of school activities, such as access difficulties due to lack of digital technologies; what are the main equipment used to access remote activities; the relationship of students' feelings and learning during the pandemic. With this, it can be inferred that remote teaching was a great challenge for EJA students, for some the difficulties of remote teaching were not enough to give up; for others, the challenges were not overcome and the possibility of continuing their studies was postponed, once again.